A sensitive and selective amperometric hydrazine sensor based on mesoporous Au/ZnO nanocomposites. (5th November 2016) - Ismail, Adel A.; Harraz, Farid A.; Faisal, M.; El-Toni, Ahmed Mohamed; Al-Hajry, A.; Al-Assiri, M.S.
Abstract: Herein, a facile synthesis of mesoporous Au/ZnO nanocomposite using photochemical reduction approach is demonstrated. The findings indicated that Au nanoparticles with size ranging from 4 to 10 nm were homogenously distributed on the surface of mesoporous ZnO. The synthesized mesoporous Au/ZnO nanocomposite as efficient electrochemical sensor towards hydrazine detection was assessed using different electrochemical techniques including cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and amperometric i-t response. The results showed that the mesoporous Au/ZnO modified GCE (glassy carbon electrode) yields an enhanced hydrazine oxidation peak at a relatively lower potential of 0.45 V vs. Ag/AgCl (Ipa = 2.6 μA, 150% higher than pure mesoporous ZnO). The amperometric detection of hydrazine at the mesoporous Au/ZnO sensor exhibits a rapid increase in the oxidation current upon the successive additions of hydrazine. The relation between the current vs. hydrazine concentration is linear (R 2 = 0.9973) over the concentration range of 0.2–14.2 μM, with a diffusion-controlled kinetic process. The sensitivity and limit of detection (LOD) of the sensor was estimated to be 0.873 μA μM − 1 cm − 2 and 0.242 μM, respectively. The key result in our synthesized mesoporous Au/ZnO nanocomposite showed significant selectivity for hydrazine detection in the presence of different interferences. Moreover, the mesoporous Au/ZnO sensor demonstrated long-term stability that exhibited high selectivity, sensitivity, repeatability, reproducibility, and fast kinetic detection within 10 s. Graphical abstract: Highlights: Mesoporous Au/ZnO was fabricated via sol gel method for electrochemical sensor. The current vs. hydrazine concentration is linear over the range of 0.2–14.2 μM. The sensitivity and limit of detection were 0.873 μA μM − 1 cm − 2 and 0.242 μM. Au-ZnO sensor showed long-term stability and fast kinetic detection within 10 s. The amperometric of Au/ZnO exhibits a rapid increase in the hydrazine oxidation.